Pengaruh Covid-19 Terhadap Imbal Hasil Saham Perusahaan Sektor Kesehatan, Teknologi, Keuangan, Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode Januari – Mei 2020 - Salsabila, Ghina; Rizkianto, Eko (Jurnal Manajemen dan Usahawan Indonesia, 2024)
This study aims to explore the impact of Covid-19 confirmed cases and Covid-19 death cases on stock return of healthcare, technology, finance, transportation, and logistic sector companies listed on Indonesia Stock Exchange in January – May 2020. Using panel data regression method, the study found that Covid-19 confirmed cases significantly affect stock return of healthcare, technology, finance, transportation, and logistic sector companies. However, there are no significant impact of Covid-19 death cases on stock return of healthcare, technology, finance, transportation, and logistic sector companies.